Quantum ideas in economics beyond quantum econometrics - Vladik Kreinovich (2018)
© 2018, Springer International Publishing AG. It is known that computational methods developed for solving equations of quantum physics can be successfully applied to solve economic problems; there is a whole related research area called quantum econometrics. Current quantum econometrics techniques are based on a purely mathematical similarity between the corresponding equations, without any attempt to relate the underlying ideas. We believe that the fact that quantum equations can be successfully applied in economics indicates that there is a deeper relation between these areas, beyond a mathematical similarity. In this paper, we show that there is indeed a deep relation between the main ideas of quantum physics and the main ideas behind econometrics.